Bean cultivars for intercropping with maize - Flesch, Roger Delmar; Espíndola, Evaristo Antonio (Pesquisa Agropecuaria Brasileira, 2014)
In order to identify bean (Phaseolus vulgaris L.) cultivars adapted to intercropping with maize (Zea mays L.), an experiment was conducted in Chapecó. SC, Brazil, during the period 1980/1983, on a Distrofic Red Soil. Twenty cultivars were evaluated and six were common in the three years period. The intercropping system utilized was 2M :38 (two rows of maize: three rows of bean). The results showed that the cultivars Carioca, EMPASC 201, Turrialba 4, lguaçú, Paraná 1 and Rio Tibagi can be intercropped with maize, and the more productives and the less productives cultivars in intercropping had the same behaviour in monoculture.